EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS VII SMP NEGERI DI KABUPATEN PACITAN - Daeka, Dalud; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of research were to find out: (1) which one providing better mathematics learning achievement, NHT or TPS or conventional learning model, (2) in the student creativity level, which one having better mathematics learning achievement, high or medium or low creativity, (3a) in each learning model (NHT, TPS and Conventional) which one providing better mathematics learning achievement, high or medium or low student learning creativity, (3b) in each student creativity level (high, medium, and low) which one providing better mathematics learning achievement, NHT or TPS or conventional learning model.This study was a quasi-experimental research. The research design used was a 3x3 factorial design. The population of research was all VII graders of Junior High Schools throughout Pacitan Regency in the school year of 2012/2013. Meanwhile the sample was taken using stratified random sampling. The sample consisted of 275 students: 92 students for experiment I class, 92 for experiment II class and 91 for control class. The instruments used to collect the data were learning creativity questionnaire and mathematics learning achievement test. From the result of research, it could be concluded that: (1) NHT learning model provided mathematics learning achievement as good as the TPS learning model did and better than the conventional learning model did, while TPS learning model provided mathematics learning achievement as good as the conventional learning model did. (2) The learning achievement of the students with high creativity was better than that of those with medium creativity, the learning achievement of the students with high creativity was better than that of those with low creativity, and the learning achievement of the students with medium creativity was as good as that of those with low creativity. (3a) On each learning model, the learning achievement of the students with high creativity was better than that of those with medium and low creativity, while the learning achievement of the students with medium creativity was as good as that of those with low creativity. (3b) On each creativity level whether high, medium or low, the mathematics learning achievement of the students taught with NHT learning model was as good as that of those taught with TPS learning model but was better than that of those taught with conventional model. And the learning achievement of the students taught with TPS learning model was as good as that of those taught with conventional model.Keywords: NHT, TPS, Conventional, Learning Creativity.